Using Fable In Developing Reading Comprehension of Grade Eight Students of SMP Negeri 2 Balaesang - Nur Alisa; Afrilia Anggreni; Sudarkam R. Mertosono (Universitas Cokroaminoto Palopo, 2024)
The objective of this research is to find out if using fable can develop the reading comprehension of grade eight students of SMP Negeri 2 Balaesang. This research used a quasi-experimental research design. The population of this research was the grade eight students of SMP Negeri 2 Balaesang. The researchers was selected using the cluster sampling technique. The sample of this research were 54 students, which were divided into 27 the students of VIIIB as a experimental group and 27 the students of VIIIA as a control group. The data were collected through the reading test that consisted of pre-test and post-test. By applying the 0.05 level significance, the researchers found that the sig value obtained (p) was lower than alpha (α) (0,000<0,05) It means that the hypothesis is accepted or using fable can develop reading comprehension of grade eight students of SMP Negeri 2 Balaesang. This research implies that the use of fable can increase students' literacy, make learning more enjoyable, and boost their activeness and engagement in the learning process.